EXPERIMENTAL PHARMACOLOGICAL STUDY OF SAPTACAKRA- SALACIA RETICULATA WIGHT. AND PUGA - ARECA CATECHU LINN. (ASHODITA AND SUDDHA) IN ALLOXAN INDUCED DIABETIC RATS - Allam, *Rama Krishna; Renu, Dixit; K.V.V.Bhaskara, Reddy (AYUSHDHARA, 2015)
In present era of science, facts established by proofs derived after careful investigations, observations and experiments and supported by accurate data can convince the people about validity of the statement. Modern medical science achieved tremendous advance in past few centuries with the help of experimental research. An experimental pharmacological study of Saptacakra and Puga (Ashodita and Asuddha) in alloxan (120 mg/kg) induced diabetic rats was done at Pharmacology Laboratory of Sree Vidyanikkethan Pharmacy College, Tirupati. The diabetic rats were divided into six groups [Control group (NC), Diabetic control group (ALX), Ashodita Puga group (ALX + ACP), Saptacakra group (ALX + SRP), Suddha Puga group (ALX + BACP) and Combination of Saptackara and Suddha Puga group (ALX + SRBACP)] with 6 animals in each groups and treated with 450 mg/kg of respective drugs. Blood sugar level and the serum lipid profiles such as total cholesterol, Phospholipids, triglycerides, LDL, V-LDL and HDL investigations and histopathological studies on liver and pancreases tissues were carried out in normal and diabetic rats. The combination of both Saptacakra and Suddha Puga (SRBACP) shows 47.02% decrease in blood sugar level. It is extremely significant (p< 0.001), though all the other groups show reduction in blood sugar level. Reduction in lipid profile was best noticed in BACP group; in particular reduction in triglycerides and improvement HDL was in combination group. Hepatoprotective action and regeneration of islets of langherans was best seen in combination group.